The rollout of internal credit risk models: Implications for the novel partial-use philosophy - Carina Schlam; Corinna Woyand (Deutsche Bundesbank, 2023)
The novel partial-use philosophy by the Basel Committee on Banking Supervision initiates a paradigm shift for banks, allowing them to permanently partially apply the internal ratings-based approach (IRBA) and not having to fully roll it out across the overall bank anymore. This raises the questions of how banks roll out the IRBA and what the consequences of partial use may be. We reveal that banks with little rollout progress over time can keep annual cost growth comparatively low. Furthermore, we find that the first implementation steps lead to the greatest risk-weighted assets reductions, which indicates that banks benefit from 'cherry-picking' by not fully rolling out the IRBA. However, we also provide tentative evidence that bank risk management improves with a progressing rollout.
Keywords: G21; G28; G32; 330; Costs; Internal Ratings-Based Approach; Partial Use; Risk Management; Risk-Weighted Assets; Rollout